2008
DOI: 10.1016/j.pain.2007.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse noxious inhibitory controls triggered by heterotopic CO2 laser conditioning stimulation decreased the SEP amplitudes induced by electrical tooth stimulation with different intensity at an equally inhibitory rate

Abstract: The purpose of this study was to investigate (1) whether selective Adelta-fiber stimulation with CO(2) laser produces a diffuse noxious inhibitory controls (DNIC) effect in the trigeminal nerve territory; and (2) whether the DNIC effect differs depending on test stimulus intensities under constant conditioning stimuli. To examine whether the CO(2) laser radiation on the dorsum of the hand selectively stimulates Adelta-fibers, laser evoked potentials (LEP) were recorded. The mean peak latency of LEP was 381.4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 52 publications
5
21
0
1
Order By: Relevance
“…A painful CO2 laser beam applied to the peripheral skin and hand induced ascending sensory signals which are mediated by Ad fibres (Kakigi et al, 1991;Oono et al, 2008), consistent with previous studies (Kakigi et al, 1989(Kakigi et al, , 1991Tran et al, 2001). A painful CO2 laser beam applied to the peripheral skin and hand induced ascending sensory signals which are mediated by Ad fibres (Kakigi et al, 1991;Oono et al, 2008), consistent with previous studies (Kakigi et al, 1989(Kakigi et al, , 1991Tran et al, 2001).…”
Section: Cpm Effectsupporting
confidence: 90%
See 2 more Smart Citations
“…A painful CO2 laser beam applied to the peripheral skin and hand induced ascending sensory signals which are mediated by Ad fibres (Kakigi et al, 1991;Oono et al, 2008), consistent with previous studies (Kakigi et al, 1989(Kakigi et al, , 1991Tran et al, 2001). A painful CO2 laser beam applied to the peripheral skin and hand induced ascending sensory signals which are mediated by Ad fibres (Kakigi et al, 1991;Oono et al, 2008), consistent with previous studies (Kakigi et al, 1989(Kakigi et al, , 1991Tran et al, 2001).…”
Section: Cpm Effectsupporting
confidence: 90%
“…2 shows individual examples of SEP waveforms during the first session with and without CO2 laser stimuli. In the first session, noxious conditioning stimuli using the CO2 laser stimuli in this study can induce CPM in accordance with our previous study in humans (Oono et al, 2008). Table 1 shows the latencies of SEP in both the first and second sessions of three types.…”
Section: Sep Waveformssupporting
confidence: 87%
See 1 more Smart Citation
“…To estimate objective pain intensity, the late component of SEPs recorded from the vertex was analyzed. On the basis of Oono's method (Oono et al, 2008), a monopolar electrode was fixed to the surface of the upper central incisors and single electrical square pulses were administrated at 1 Hz. In this study, stimuli inducing bearable pain sensation (VAS = 5 -7) were administered.…”
Section: Pain Research Using Sepsmentioning
confidence: 99%
“…Largest effect of CPT were found near pain threshold and no effect for stimuli below pain threshold [115]. On the contrary, laser modulating stimuli resulted in almost equal inhibitory effects regardless of stimulus amplitudes of electrical tooth stimulation [111]. Talbot et al [134] also showed inhibition of both perceived non-noxious and noxious heat stimuli by CPT.…”
Section: Discussionmentioning
confidence: 98%